Effect of Stiffness of Rolling Joints on the Dynamic Characteristic of Ball Screw Feed Systems in a Milling Machine - Dazhong Wang; Yan Lu; Tongchao Zhang; Keyong Wang; Akira Rinoshika (Shock and Vibration)
Dynamic characteristic of ball screw feed system in a milling machine is studied numerically in this work. In order to avoid the difficulty in determining the stiffness of rolling joints theoretically, a dynamic modeling method for analyzing the feed system is discussed, and a stiffness calculation method of the rolling joints is proposed based on the Hertz contact theory. Taking a 3-axis computer numerical control (CNC) milling machine set ermined as a research object, the stiffness of its fixed joint between the column and the body together with the stiffness parameters of the rolling joints is evaluated according to the Takashi Yoshimura method. Then, a finite element (FE) model is established for the machine tool. The correctness of the FE model and the stiffness calculation method of the rolling joints are validated by theoretical and experimental modal analysis results of the machine tool’s workbench. Under the two modeling methods of joints incorporating the stiffness parameters and rigid connection, a theoretical modal analysis is conducted for the CNC milling machine. The natural frequencies and modal shapes reveal that the joints’ dynamic characteristic has an important influence on the dynamic performance of a whole machine tool, especially for the case with natural frequency and higher modes.